Smart Contracts Business Model Canvas - Silviu OJOG; Alina-Andrea MIRON (Informatică economică, 2025)
Smart Contracts are the central piece of Ethereum and other compatible blockchains. Their role is to build trusted functionality that unknown parties can interact with. However, their value proposition can be undermined by different security exploits. In many cases, vulnerabilities are overlooked not due to neglect but due to a systematic approach in the review process. This paper aims to appeal to existing frameworks for understanding the business context and provide standardized thinking on auditing smart contracts. The power of a framework lies in the fact that it ensures that auditors do not overlook critical aspects of their vulnerability.